2022
DOI: 10.3390/jpm12060937
|View full text |Cite
|
Sign up to set email alerts
|

Increased Orbital Muscle Fraction Diagnosed by Semi-Automatic Volumetry: A Risk Factor for Severe Visual Impairment with Excellent Response to Surgical Decompression in Graves’ Orbitopathy

Abstract: Graves’ orbitopathy (GO) leads to increased orbital tissue and causes symptoms such as exophthalmos, functional complaints, or dysthyroid optic neuropathy. Different GO types with fat and/or muscle enlargement were identified, and increased muscle appears to particularly influence visual status and treatment response. The current study examines visual parameters dependent on orbital muscle volume fraction in a surgically treated GO cohort. After volumetric analysis of the preoperative orbital content, 83 orbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Graves’ orbitopathy (GO), an increase in orbital fat and/or muscle tissue due to autoimmune inflammation, can cause proptosis, double vision, and/or dysthyroid optic neuropathy (DON). Steiert et al examined visual parameters dependent on the orbital muscle volume fraction in a surgically treated GO cohort and suggested that the orbital muscle volume factor should be addressed during treatment decisions, while early orbital decompression should be considered particularly in decreased vision with orbital muscle enlargement [ 8 ]. In a way that is different to the traditional staged GO management order (decompression and then muscle surgery or lid surgery), Hsieh et al suggested that orbital decompression combined with strabismus surgery by experienced surgeons can achieve satisfactory outcomes in selected patients, especially for those with symmetry of orbitopathy, relatively simple strabismus and mild proptosis [ 9 ].…”
mentioning
confidence: 99%
“…Graves’ orbitopathy (GO), an increase in orbital fat and/or muscle tissue due to autoimmune inflammation, can cause proptosis, double vision, and/or dysthyroid optic neuropathy (DON). Steiert et al examined visual parameters dependent on the orbital muscle volume fraction in a surgically treated GO cohort and suggested that the orbital muscle volume factor should be addressed during treatment decisions, while early orbital decompression should be considered particularly in decreased vision with orbital muscle enlargement [ 8 ]. In a way that is different to the traditional staged GO management order (decompression and then muscle surgery or lid surgery), Hsieh et al suggested that orbital decompression combined with strabismus surgery by experienced surgeons can achieve satisfactory outcomes in selected patients, especially for those with symmetry of orbitopathy, relatively simple strabismus and mild proptosis [ 9 ].…”
mentioning
confidence: 99%